ANALISIS PENGARUH TIKTOKSHOP TERHADAP PENINGKATAN MINAT BERWIRAUSAHA MAHASISWA (STUDI KASUS PADA MAHASISWA FEB UNM) - Maharani, Radysa Puteri; Asri Irwanti, A.Azzahra; Ida Ariqah, Nurul; Mubarak, Abdullah; Jibriyanti, Jibriyanti; Nursanti, Nursanti; Rahman Ali, Andi Fazlur (LP2M Universitas Perjuangan Tasikmalaya, 2025)
This study aims to evaluate the impact of TikTok Shop as an e-commerce platform on entrepreneurial interest among students of the Faculty of Economics and Business, Makassar State University (FEB UNM). The method used is a quantitative approach with simple linear regression analysis, where data is collected through questionnaires from active students of FEB UNM. The results showed that TikTok Shop has a significant positive influence on entrepreneurial interest with a coefficient of determination of 77%. This study also confirms the importance of increasing digital literacy and using TikTok Shop for business. Hopefully, the results of this study can provide practical information for students and theoretical contributions to the development of entrepreneurship studies. Suggestions for future research include further exploration of the long-term impact of TikTok Shop on the sustainability of students' businesses.